2015
DOI: 10.1016/j.ultrasmedbio.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive in Vivo Characterization of Human Carotid Plaques with Acoustic Radiation Force Impulse Ultrasound: Comparison with Histology after Endarterectomy

Abstract: Ischemic stroke from thromboembolic sources is linked to carotid artery atherosclerotic disease with a trend toward medical management in asymptomatic patients. Extent of disease is currently diagnosed by noninvasive imaging techniques that measure luminal stenosis, but it has been suggested that a better biomarker for determining risk of future thromboembolic events is plaque morphology and composition. Specifically, plaques that are composed of mechanically-soft lipid/necrotic regions covered by thin fibrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…To validate simulation results, data were compared against two in vivo examples of carotid plaque with histologically-verified fibrous caps [26]. As was done in the simulation study, in vivo data were motion tracked with eight kernel sizes whose length was determined with respect to the center frequency of the tracking pulses (6.15 MHz).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate simulation results, data were compared against two in vivo examples of carotid plaque with histologically-verified fibrous caps [26]. As was done in the simulation study, in vivo data were motion tracked with eight kernel sizes whose length was determined with respect to the center frequency of the tracking pulses (6.15 MHz).…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that ARFI can discriminate necrotic/lipid from fibrous/calcified regions, which appear as areas of relatively-high displacement and relatively-low displacement, respectively. Anecdotally, some of these studies have shown that ARFI can visualize a FC in vivo as an area of low-displacement covering an area of high-displacement [26], however, the capability to quantify FC thickness has yet to be rigorously explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a previously described protocol 16 , a total of 25 patients undergoing clinically indicated CEA were recruited from UNC Hospitals. Inclusion criteria included asymptomatic carotid artery disease with >60% Doppler-indicated stenosis and unresponsive to medical management (i.e patients with known disease who are being managed with antihypertensive medication, cholesterol medication and smoking cessation, who have progression of stenosis implied unresolved naive to medical management) or symptomatic carotid artery disease with a stenosis suspected to be the source of emboli.…”
Section: Methodsmentioning
confidence: 99%
“…ARFI imaging was performed with the carotid artery in longitudinal orientation using a Siemens Acuson Antares (Siemens Medical Solutions USA Inc., Ultrasound Division) and a VF7-3 linear array 16 . Data acquisition, processing, and image rendering methods are described in the online-only Data Supplement.…”
Section: Methodsmentioning
confidence: 99%